Optimization of Oil Palm Empty Fruit Bunches Cellulose-based Bioplastic Formulation with Response Surface Methodology (RSM) - Herianti, Putri; Andhika Permata, Deivy; Neswati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Bioplastics are one of the alternatives to replace synthetic plastics. Bioplastics are plastics made from natural materials readily decomposed by microorganisms so that they are environmentally friendly. Oil Palm Empty Fruit Bunches (OPEFB) have cellulose content that can be utilized as raw material in the manufacture of bioplastics. This research aims to determine the best formulation of OPEFB cellulose-based bioplastics as environmentally friendly packaging. The method used in this research is the Response Surface Methodology (RSM) optimization method in the Mixture (Optimal Custom Design) section found in the Design Expert version 13 application. The factors analyzed in making bioplastics are glycerol, starch, CMC, and chitosan. Bioplastic observations include tensile strength, elongation, elasticity, thickness, water resistance, and biodegradation. The result of OPEFB cellulose obtained in this study is 71.88%, where the cellulose produces strong bioplastic properties. The optimum solution of bioplastic formulation produced is the addition of glycerol of 0.89 g, starch of 2.99 g, CMC of 2.11 g, and chitosan of 3 g Laboratory verification responses produced are tensile strength of 12 MPa, elongation of 31.34%, elasticity of 890.67 MPa, thickness of 0.25 mm, water resistance of 88.95%, and biodegradation of 4.34%/day. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and Infrastructure SDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 14: Life Below WaterSDG 15: Life on LandSDG 17: Partnerships for the Goals